IMPLEMENTASI MODEL PROBLEM BASED LEARNING BERBANTUAN TABEL BERMAIN PERKALIAN UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK KELAS II SDN PALEBON 03 - Octavianingsih, Endah Ayu; Joko Siswanto; Suharni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning activity is an activity that involves the body and mind in interconnected learning activities, thereby producing optimal learning activity. Based on observations in the field, the following facts were found: 1) classroom learning processes still center around the teacher; 2) student activities are still insufficient during the teaching and learning process. This research aims to describe the extent to which student learning activities increase with the application of problem-based learning models assisted by the Multiplication Play Table media. The Classroom Action Research shows that applying the problem-based learning model assisted by the Multiplication Play Table media can enhance student learning activities in Grade II at SDN Palebon 03 Semarang. This can be seen from the fulfillment of success indicators in increasing student learning activities, with average scores in the pre-cycle at 56, increasing to 69 in cycle I, and finally achieving a score of 77 at the end of cycle II.